`Pengaruh Earnings Management terhadap Stock Returns pada Perusahaan LQ45 - Desy Arisandi Halim (Business Accounting Review, 2017)
The purpose of this research was to find the relationship of earnings management and the stock return. This study used a quantitative method with secondary data taken from the firms’ annual reports. The sample of this study was the companies that listed in Indonesia stock market index, LQ45, for 6 years from 2010 until 2015. The analytical technique was used panel data regression with software STATA to test the relationship among variables. This study also used IBM SPSS Statistics 23 to determine the coefficient for discretionary accruals (the proxy of earnings management) from modified Jones model. The outcome from this study showed that there was no relationship between earnings management and stock returns.